2002
DOI: 10.1021/om020395q
|View full text |Cite
|
Sign up to set email alerts
|

Cyclohexadienyl Niobium Complexes and Arene Hydrogenation Catalysis

Abstract: Hydrogenolysis of R[P2N2]NbCH2SiMe3 (where R[P2N2] = RP(CH2SiMe2NSiMe2CH2)2PR; R = cyclohexyl, Cy, or phenyl, Ph) in benzene or toluene causes hydride addition to the aromatic solvent resulting in the formation of the π-bonded complexes R[P2N2]Nb(η5-C6H7) (R = Cy, 1; R = Ph, 2) and R[P2N2]Nb(η5-C7H9) (R = Cy, 3; R = Ph, 4) in benzene and toluene, respectively. Performing the hydrogenation at a higher pressure of 29 atm at room temperature causes the catalytic hydrogenation of benzene to cyclohexane as determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Recently Fryzuk et al have reported cyclohexadienyl complexes of niobium amidophosphine ligands. 21 Tilley and Gavenonis have also demonstrated the formation of an η 5 -cyclohexadienyl ring by hydride transfer from tantalum to an ortho-aryl ring in an amido ligand. In this case reversible transfer to the meta-position of a [Ta-NHAr*] ring (Ar* ) 2,6-dimesitylphenyl) takes place.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently Fryzuk et al have reported cyclohexadienyl complexes of niobium amidophosphine ligands. 21 Tilley and Gavenonis have also demonstrated the formation of an η 5 -cyclohexadienyl ring by hydride transfer from tantalum to an ortho-aryl ring in an amido ligand. In this case reversible transfer to the meta-position of a [Ta-NHAr*] ring (Ar* ) 2,6-dimesitylphenyl) takes place.…”
Section: Methodsmentioning
confidence: 97%
“…The first key intermediate proposed in the mechanistic pathway (Scheme 4) is an η 5 -cyclohexadienyl formed by initial attack of a metal-hydride on an arene ring. 21 This has previously been missing in aryloxide chemistry. Recently Fryzuk et al have reported cyclohexadienyl complexes of niobium amidophosphine ligands.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to [D 6 ]benzene, neat [D 8 ]toluene is more rapidly hydrogenated with nearly twice the TON over the first 20 h (Table ; Figures S28 and S38, SI). This is surprising, as in the case of the macrocyclic phosphine amide R [P 2 N 2 ]Nb(CH 2 SiMe 3 ), the catalytic competency of the niobium complex drops precipitously from benzene to toluene . Rothwell's niobium arene hydrogenation catalysts also show a decrease in relative rate from benzene to toluene, though no other correlation between hydrogenation rates and sterics can be drawn from his system .…”
Section: Methodsmentioning
confidence: 99%
“…This is surprising, as in the case of the macrocyclic phosphinea mide R [P 2 N 2 ]Nb(CH 2 SiMe 3 ), the catalytic competency of the niobium complex drops precipitously from benzene to toluene. [7] Rothwell's niobium arene [b] [D 6 ]cyclohexane 1.0 0.05 2.0 [D 8 ]toluene [b] [D 8 ]methylcyclohexane1 .8 0.09 2.9 naphthalene tetralin 4.4 0.22 7.4 anthracene octahydroanthracene 4.6 0.23 6.5 styrene [c] ethylbenzene9 .0 0.45 13.9 [c] hydrogenation catalysts also show ad ecrease in relative rate from benzene to toluene, thoughn oo ther correlation between hydrogenation rates and sterics can be drawn from his system. [1b] However, it should be noted that, when using fewer equivalents of toluene (20 equiv) in [D 12 ]cyclohexane with 1, the decrease in the rate of hydrogenation is pronounced (TON < 0.7 after 20 h) ( Figure S33, Supporting Information).…”
mentioning
confidence: 99%
“…101 Silyl derivatives of group 5 organometallic complexes have been investigated including intramolecular C-H activation of silyl ligands by tantalum() imido moieties 102 and the formation of an unusual imido-bridged 1,3-disilaniocyclobutane 11 from reaction between [Nb(η 5 -C 5 H 5 )(H)(SiMe 2 I) 2 ] and H 2 NEt 2 . 103 Hydrogenation of aromatics 104 and intramolecular hydride transfers to aromatic rings have been studied and an investigation into dihydrogen addition to [Ta(CH 2 )-(η 5 -C 5 Me 5 ) 2 (H)] using parahydrogen has also been reported. 105 Insertion processes of a series of niobium() alkyl and alkyne complexes have been investigated and supported by DFT calculations 106 and the coupling of 1-aza-1,3-butadiene and iminoacyl ligands to give amido-imido complexes of tantalum() reported.…”
Section: Vanadium Niobium Tantalummentioning
confidence: 99%